Perancangan Game Android Tentang Kebersihan Sungai untuk Anak Usia 7-12 Tahun di kudus - Indra Ardiansyah; Jasson Prestiliano; Birmanti Setya Utami (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
River pollution has become one of the serious environmental issues in Indonesia, including in the Gelis River in Kudus City. The lack of public awareness—especially among the younger generation—in maintaining river cleanliness highlights the need for effective and engaging educational media. This study aims to design an Android-based educational game as an interactive learning tool for children aged 7 to 12 years to raise their awareness about the importance of keeping rivers clean. The research method used is Research and Development (R&D), employing the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The game developed, titled RiverCourse: Petualangan Menjaga Sungai (RiverCourse: The Adventure of Protecting the River), features a sidescrolling mechanic with a visual style combining pixel art and cartoons, suited to the cognitive development stage of children. Testing was conducted on the target age group through observation and simple questionnaires.